MountainRise, Volume 6, Number 2 - Coulter Faculty Commons (2020)
Volume 6, Number 2 (2010). MountainRise, an open, peer-reviewed, international electronic journal, was published by the Coulter Faculty Commons for Excellence in Teaching & Learning at Western Carolina University. Originating in the ancient mountains of western North Carolina, MountainRise served as an international vehicle for the Scholarship of Teaching & Learning (SoTL). MountainRise applied insightful scholarly methodologies to the processes of teaching and learning. The aim of the journal was to foster a higher education culture that embraced innovation in teaching and learning.